Penguatan Interelasi Guru dan Kurikulum Menuju PAUD Berkualitas - Edi Waluyo; Amirul Mukminin; Bagus Kisworo; Wantoro, Wantoro; Nabila Zakiyyatul Af'idah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Teachers and curriculum are components that greatly influence the implementation and achievement of quality education. The role of teachers as implementers of learning in the classroom, greatly requires the role of the curriculum used as a guideline in learning, and vice versa, the curriculum requires the role of professional teachers as implementers of the curriculum in the classroom. The purpose of the community service activities that have been carried out is to strengthen the interrelationship between teachers and the curriculum, so that a strong relationship occurs as an effort towards the implementation of quality ECE. The method of community service activities uses participatory action research (PAR), with the aim of learning in overcoming problems and fulfilling needs in the community. In detail, the implementation of this community service activity is to meet the needs of ECE educators, by providing training through workshops and mentoring activities that are implemented in ECE institutions. Based on the objectives and methods used, this community service activity is to lead teachers and the curriculum in implementing quality ECE learning and development institutions. The implementation of the curriculum supported by professional teachers is capital for institutions in providing quality stimulation and learning services for early childhood. So the stronger the interrelationship between teachers and the curriculum, the easier it will be for ECE institutions to provide quality education services.